FENOMENA KERUSAKAN RIGID PAVEMENT PADA JALAN TOL PADALEUNYI KM 09+300 B (ARAH PADALARANG) - Iman Murtosidi; Saksono, MSc (Direktorat Bina Teknik Jalan dan Jembatan, 2005)
This paper of in a flash give picture concerning interesting phenomenon is avalanche of rigid pavement at Padalarang - Cileunyi Toll road, that happened at 11 October 2002 on 3.00 p.m., and information to society, especually to organizer of toll to danger which is can happened at woke up road; street pavement rigid above land of softening. In the beginning behavioral rigid pavement of me as glazer of elastic foundation with natural frequency. Degradation of land; ground local/sub of soil that happened change rigid pavement become semi cantilever, so that traffic burden vibration frequency turn into low natural frequency. Dynamic burden of traffic result natural pavement rigid of vibration flexural. More deflection downwards and more bigly (amplification) if only frequency of forced its value vibration much the same to with frequency of free vibration. Because of rigid pavement deflection downwards detained by free lean concrete conversely deflection to up wards,hence happened by avalanche at rigid pavement accompanied by explosion because stiff concrete characteristic/brittle